A Research on Financial Performance of Medium Sized Companies under Corporate Governance in India: Examining the Impact of Corporate Governance on Financial Performance of Medium Sized Family Managed Companies in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
National Foundation for Corporate Governance (NFCG) was set up by the Ministry of Corporate Affairs, Government of India, in organization with Confederation of Indian Industry (CII), Institute of Company Secretaries of India (ICSI) and Institute of Chartered Accountants of India (ICAI). In the year 2010, ICWAI and the National Stock Exchange additionally joined NFCG as its accomplices. NFCG’s mission is to advance better Corporate Governance practices in India by encouraging a culture for advancing great governance, deliberate consistence and successful interest of various partners and make a framework for best practices, structure, processes and morals in business. Along these lines it means to have a huge effect to the Indian Corporate Sector by raising the principles of Corporate Governance in India. The investigation depends on auxiliary research which included a point by point examination of corporate governance practices and financial performance of a chose test of medium sized companies. The uniqueness of our Study lies in the way this is the first occasion when that the impact of corporate governance has been evaluated on the financial performance of family oversaw companies in India. The other particular element of our Study is that for concentrate the corporate governance practices of these companies we have considered not just the Mandatory and Non‐mandatoryRecommendatory necessities under SEBI proviso 49 yet in addition the measures taken by the companies deliberately as proposed by the Ministry of Corporate Affairs in its Guidelines.